Polystyrene nanoplastics mediate oxidative stress, senescence, and apoptosis in a human alveolar epithelial cell line - Milillo, Cristina; Aruffo, Eleonora; Di Carlo, Piero; Patruno, Antonia; Gatta, Marco; Bruno, Annalisa; Dovizio, Melania; Marinelli, Lisa; Dimmito, Marilisa Pia; Di Giacomo, Viviana; Paolini, Cecilia; Pesce, Mirko; et al. (Frontiers in Public Health, 2024)
Background Nanoplastics, an emerging form of pollution, are easily consumed by organisms and pose a significant threat to biological functions due to their size, expansive surface area, and potent ability to penetrate biological systems. Recent findings indicate an increasing presence of airborne nanoplastics in atmospheric samples, such as polystyrene (PS), raising concerns about potential risks to the human respiratory system. Methods This study investigates the impact of 800 nm diameter-PS nanoparticles (PS-NPs) on A549, a human lung adenocarcinoma cell line, examining cell viability, redox balance, senescence, apoptosis, and internalization. We also analyzed the expression of hallmark genes of these processes. Results We demonstrated that PS-NPs of 800 nm in diameter significantly affected cell viability, inducing oxidative stress, cellular senescence, and apoptosis. PS-NPs also penetrated the cytoplasm of A549 cells. These nanoparticles triggered the transcription of genes comprised in the antioxidant network [SOD1 (protein name: superoxide dismutase 1, soluble), SOD2 (protein name: superoxide dismutase 2, mitochondrial), CAT (protein name: catalase), Gpx1 (protein name: glutathione peroxidase 1), and HMOX1 (protein name: heme oxygenase 1)], senescence-associated secretory phenotype [Cdkn1a (protein name: cyclin-dependent kinase inhibitor 1A), IL1A (protein name: interleukin 1 alpha), IL1B (protein name: interleukin 1 beta), IL6 (protein name: interleukin 6), and CXCL8 (protein name: C-X-C motif chemokine ligand 8)], and others involved in the apoptosis modulation [BAX (protein name: Bcl2 associated X, apoptosis regulator), CASP3 (protein name: caspase 3), and BCL2 (protein name: Bcl2, apoptosis regulator)]. Conclusion Collectively, this investigation underscores the importance of concentration (dose-dependent effect) and exposure duration as pivotal factors in assessing the toxic effects of PS-NPs on alveolar epithelial cells. Greater attention needs to be directed toward comprehending the risks of cancer development associated with air pollution and the ensuing environmental toxicological impacts on humans and other terrestrial mammals.